Nonlinear Fourier Transforms and the mKdV Equation in the Quarter Plane. Issue 1 (16th June 2015) - Lenells, Jonatan
Abstract : The unified transform method introduced by Fokas can be used to analyze initial‐boundary value problems for integrable evolution equations. The method involves several steps, including the definition of spectral functions via nonlinear Fourier transforms and the formulation of a Riemann‐Hilbert problem. We provide a rigorous implementation of these steps in the case of the mKdV equation in the quarter plane under limited regularity and decay assumptions. We give detailed estimates for the relevant nonlinear Fourier transforms. Using the theory of L 2 ‐RH problems, we consider the construction of quarter plane solutions which are C 1 in time and C 3 in space.